2009
DOI: 10.1099/vir.0.013425-0
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of eggplant latent viroid RNA processing in Chlamydomonas reinhardtii chloroplast

Abstract: Viroids of the family Avsunviroidae, such as eggplant latent viroid (ELVd), contain hammerhead ribozymes and replicate in the chloroplasts of the host plant through an RNA-based symmetrical rolling-circle mechanism in which oligomeric RNAs of both polarity are processed to monomeric linear RNAs (by cleavage) and to monomeric circular RNAs (by ligation). Using an experimental system consisting of transplastomic lines of the alga Chlamydomonas reinhardtii, a mutational analysis of sequence and structural element… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
25
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 37 publications
4
25
0
2
Order By: Relevance
“…Dangeard expressing different ELVd mutant forms indicates that the viroid sequence requirements for cleavage and ligation are different. More specifically, a quasi-double-stranded structure in the central part of the ELVd molecule (folded in the predicted minimum free-energy conformation) containing the ligation site in an internal loop motif seems involved in ELVd circularization in a chloroplastic context (33). This result suggested that an RNA ligase activity of chloroplastic localization, able to recognize the viroid ligation conformation, likely mediates ELVd circularization (33).…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…Dangeard expressing different ELVd mutant forms indicates that the viroid sequence requirements for cleavage and ligation are different. More specifically, a quasi-double-stranded structure in the central part of the ELVd molecule (folded in the predicted minimum free-energy conformation) containing the ligation site in an internal loop motif seems involved in ELVd circularization in a chloroplastic context (33). This result suggested that an RNA ligase activity of chloroplastic localization, able to recognize the viroid ligation conformation, likely mediates ELVd circularization (33).…”
mentioning
confidence: 75%
“…Reaction products were mixed with 1 volume of loading buffer (98% formamide, 10 mM Tris-HCl [pH 8.0], 1 mM EDTA, 0.0025% xylene cyanol, 0.0025% bromophenol blue), denatured by heating for 2 min at 95°C, and separated by denaturing PAGE. ELVd (ϩ) RNAs were detected by Northern blot hybridization using a 32 P-labeled ELVd (Ϫ) RNA probe as previously described (33). In the circularization assay of the (ϩ) and (Ϫ) monomeric linear self-cleavage forms of all viroids (ASBVd, PLMVd, CChMVd, and ELVd), 1 mM ATP was replaced by 5 Ci of [␥-…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reaction products were mixed with 1 vol of loading buffer [98% (vol/vol) formamide, 10 mM Tris·HCl (pH 8.0), 1 mM EDTA, 0.0025% xylene cyanol, 0.0025% bromophenol blue] and separated by denaturing PAGE in 5% (wt/vol) gels including 8 M urea in TBE buffer. RNAs were electroblotted to positively charged nylon membranes (Nytran SPC; Whatman), cross-linked by irradiation with 1.2 J/cm 2 UV light (Vilber Lourmat), and analyzed by hybridization using a complementary 32 Plabeled RNA probe as previously described (29). In some experiments, 1 mM ATP was excluded from the RNA circularization assay or replaced by 1 mM CTP, 1 mM GTP, 1 mM UTP, or all of the possible combinations of each two NTPs at 1 mM each.…”
Section: Methodsmentioning
confidence: 99%
“…Template switching also highlights the impact that replication can have on evolution because, in the three classes of small RNA replicons here compared, there are examples of mosaic sequences most likely emerging from recombination events between pre-existing RNAs; actually, the HDV genome itself has most stable secondary structure predicted for the viroid RNA. 79 Alternatively, circularization of chloroplastic viroids might be an RNA-mediated mechanism: (i) catalyzed by the hammerhead ribozyme and producing a 3',5'-phosphodiester linkage, thus resembling the mode of action of the hairpin ribozyme (see below) or (ii) autocatalyzed (self-ligation) and producing an atypical 2',5'-phosphodiester bond. 80 A critical assessment of these options has been presented elsewhere in reference 57.…”
Section: Additional Effects Of Replication and Concluding Thoughtsmentioning
confidence: 99%